A Systematic Scoping Review of Patient-specific Devices in Operative Management of Scaphoid Nonunion - Michael Roberts, BBiomed (Hons), MD; Susie Lee, BPhysio, MD, MTrauma; Amy Allen, BSc, MD; Joshua Bloor, BExSportSc, MD; Rose Nicol, BSc, MD; Eliza Whiteside, BSc, PGCert AcadPrac, PhD; Vivek Shridhar, MBBS, FRACS (Ortho), FAOrthoA; Paulomi (Polly) Burey, BEng, GCertEd, PhD; Tristan Shelley, BEng, PhD; Christopher Wall, MBBS, BMedSc, FRACS, FAOrthA (JBJS Open Access)
Abstract. Scaphoid nonunion is a complication that occurs in 5-10% of patients who sustain an acute scaphoid fracture. There is no superior method for managing scaphoid nonunion that has been established in the current literature. The use of patient specific devices has been explored as a way to improve surgical management of scaphoid nonunion. 3D printing has made the production of patient specific devices more accessible. CT and MRI images can be used to model devices such as anatomic models and surgical guides. In this review we aim to discuss the current evidence for the use of patient specific devices for managing chronic scaphoid nonunion and demonstrate their different uses. A scoping review of peer-reviewed literature, existing patent applications, and grey literature was performed. Although the current research has demonstrated some possible benefits such as reduction in surgical time and accuracy of restoration of anatomy, further investigation with comparative studies is required to make conclusions about the superiority of these techniques over standard freehand techniques.